2022
DOI: 10.1186/s12879-022-07623-9
|View full text |Cite
|
Sign up to set email alerts
|

Increased transmissibility of SARS-CoV-2 alpha variant (B.1.1.7) in children: three large primary school outbreaks revealed by whole genome sequencing in the Netherlands

Abstract: Background Variant of concern (VOC) SARS-CoV-2 alpha variant (B.1.1.7) was the dominant strain in the Netherlands between March 2021–June 2021. We describe three primary school outbreaks due to the alpha variant using whole genome sequencing with evidence of large-scale transmission among children, teachers and their household contacts. Method All outbreaks described were investigated by the South Limburg Public Health Service, the Netherlands. A c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…We identified 2097 records (1791 from PubMed, 306 from medRxiv, and 2 from reference lists of eligible articles) published between June 18, 2021, and March 8, 2022 (eFigure 1 in the Supplement). Fifty-eight new studies (eTable 2 in the Supplement) were combined with 77 studies from our previous review (see eTable 3 in the Supplement for references included from our previous review), with Figure 1 showing household SAR by study period, resulting in 135 total studies representing 1 375 806 contacts from 36 countries. Four of the new studies were preprints in our previous review that were subsequently published.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 2097 records (1791 from PubMed, 306 from medRxiv, and 2 from reference lists of eligible articles) published between June 18, 2021, and March 8, 2022 (eFigure 1 in the Supplement). Fifty-eight new studies (eTable 2 in the Supplement) were combined with 77 studies from our previous review (see eTable 3 in the Supplement for references included from our previous review), with Figure 1 showing household SAR by study period, resulting in 135 total studies representing 1 375 806 contacts from 36 countries. Four of the new studies were preprints in our previous review that were subsequently published.…”
Section: Resultsmentioning
confidence: 99%
“…This reflects new variants and changing vaccination coverage. From highest to lowest, the overall household SARs were 42.7% (95% CI, 35.4%-50.4%) for Omicron (7 studies), 36.4% (95% CI, 33.4%-39.5%) for Alpha (11 studies), 29.7% (95% CI, 23.0%-37.3%) for Delta (16 studies), and 22.5% (95% CI, 18.6%-26.8%) for Beta (3 studies) (Figure 2). High heterogeneity was found among studies for Omicron ( I 2 = 98.2%; P < .001) and Delta ( I 2 = 99.1%; P < .001), moderate for Alpha ( I 2 = 59.6%; P < .001), and low for Beta ( I 2 = 2.6%; P = .79).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, three of the nine positive cases were children. Gorgels et al 26 have recently reported three large primary school outbreaks in the Netherlands, suggesting increased transmissibility of the VOC Alpha among children aged 5–12. The higher prevalence of this variant in children was also observed in studies carried out in Argentina 27 and Turkey 28 …”
Section: Discussionmentioning
confidence: 99%
“…We selected this building for testing as the classrooms most closely resembled the classrooms in the K-12 schools in the local districts based on size and ventilation. Classroom A had an approximate area and volume of 51m 2 and 125m 3 , respectively. Classroom B had an approximate area and volume of 96m 2 and 235m 3 , respectively.…”
Section: Standard Classroom Set-upmentioning
confidence: 99%
“…The COVID-19 pandemic has proven to be a persistent problem that will require a multifaceted approach to solve 1 , particularly in the wake of the appearance of newer, more easily transmitted variants of the virus [2][3][4] . Indoor air quality is highly linked to COVID-19 mitigation as it is primarily spread through respiratory aerosols (particles) dispersed by infected individuals [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%